Modeling Soil Carbon Under Diverse Cropping Systems and Farming Management in Contrasting Climatic Regions in Europe - Begum, Khadiza; Zornoza, Raul; Farina, Roberta; Lemola, Riitta; Álvaro-Fuentes, Jorge; Cerasuolo, Marianna (Frontiers in Environmental Science, 2022)
Sustainable agriculture has been identified as key to achieve the 2030 Agenda for the Sustainable Development Goals aiming at ending poverty and hunger, and addressing climate change, while maintaining natural resources. Soil organic carbon (SOC) sequestration is a key soil function for ecosystem services, and storing carbon (C) in soil by changing traditional management practices can represent an important step towards the development of more sustainable agricultural systems in Europe. Within the European project Diverfarming, the process-based ecosystem model ECOSSE was modified and evaluated in four long term experiments (>8 years) to assess the impact of crop diversification and agricultural management in SOC dynamics. ECOSSE was able to simulate SOC under dry conditions in Mediterranean regions in Spain and Italy. In the site of Murcia, Spain, the addition of manure and cover crop in the diversified systems produced an increase of SOC in nine years, when compared to the conventional management (16% measurement, 32% simulations). The effect of tillage on SOC stock in dry soil, in Foggia, Italy and Huesca, Spain, was also modelled, and a positive impact on SOC was predicted when no tillage is practiced. Finally, ECOSSE was used to understand the impact of diversifications in Boreal regions, Finland, where different proportions of legumes and grass were considered in a four-year crop rotation compared to conventional cereal rotations. Experiments and modelling showed that the loss of SOC in conventional cereal was compensated when grass was introduced in the rotations. A good agreement (RMSE <10%) and a non-significant bias were observed between model and data for all sites. Mitigation scenarios considered in the modelling analysis for the test site Huesca showed that an integrated management of no tillage and manure is the best strategy to increase SOC, ~51%, compared to the baseline scenario (current farmers practice). This study demonstrated the ability of the modified version of ECOSSE to simulate SOC dynamics in diversified cropping systems, with various soil management practices and different climatic conditions. Further studies linking SOC simulations to indicator of sustainability across various European pedoclimatic regions are ongoing.